Ultra-Sound Guided Fine Needle Aspiration Cytology in Diagnosis of Space Occupying Lesions of Liver with Special Emphasis on Hepato-Cellular Carcinoma (International Journal of Scientific Research and Management (IJSRM), 2017)
Background The evaluation and management of various hepatic lesions is a common clinical problem and their appropriate clinical management depends on accurate diagnoses. Aims: To study the cytomorphological features of distinctive non-neoplastic and neoplastic lesions of the liver and to evaluate the sensitivity, specificity and diagnostic accuracy of ultrasonography (USG)-guided fine needle aspiration cytology (FNAC) in the diagnosis of liver diseases. Materials and Methods: The study was performed on patients who came with SOL in liver on ultrasonography, with normal range of prothrombin time index in SMS hospital, Jaipur. Procedure was performed on 172 patients from 2 January 2016 to 16 sepetember 2016. USG Guided FNAC performed after getting an informed consent & with the help of a radiologist. Relevant clinical and serological details were obtained from every patient . Results: The mean age at presentation 56.47 years (25-95 years), ratio was almost equal male to female , male patient were 91(52.9%) and female were 81(47.09%) out of 172. Adequate sample were 148(86.04) and inadequate sample were 24 out of 172 patients. The cytological diagnosis of non neoplastic lesion were total 10 in which granuloma 01(10%),liver abscess 4(40%),regenerating nodule 1(10%) , fatty liver 2(20%), cystic lesion 1(10%) and inflammatory lesions 1(10%). Neoplastic lesion were(135) more common than non neoplastic lesions . The majority of neoplastic lesion were metastatic tumor 104(77.03%), followed by primary HCC23 (17.3%), unclassified malignancies 4(2.96%), cholangiocarcinoma 4 (2.96%) out of total 135 cases. The overall diagnostic accuracy of FNAC was 97.82% with a sensitivity and specificity of 96.87 and 100% respectively. Conclusion - USG-guided FNAC of the liver is a safe, simple, cost-effective and accurate method for cytological diagnosis of hepatic diffuse, focal/nodular and cystic lesions with good sensitivity and specificity